Development of Community Based Tourism (CBT) by Utilizing Local Resources of Krachaeng Subdistrict, Phra Nakhon Si Ayutthaya Province - Waiyakrud, Kanmanee; Nuiplot, Nalin-on (Area Based Development Research Journal, 2023)
Krachaeng subdistrict, Bang Sai district, Phra Nakhon Si Ayutthaya province of Thailand, is a farming community abundant in community resources, including historical sites, agricultural learning resources, and community wisdom. It was also previously designated as a development area under the One Tambon One Product (OTOP) Nawatwithi project. This research aims to develop community-based tourism (CBT) in Krachaeng subdistrict, Bang Sai district, Phra Nakhon Si Ayutthaya province, through participatory action research. The research process involved three main steps: 1) Creating understanding and awareness, 2) Exploring the community's potential in terms of wisdom, economy, and physical environment, and 3) Developing tourism potential by establishing community products that meet standards, training community interpreters, developing community learning bases, designing tourism programs, and enhancing public relations through various media platforms. The research findings indicate the successful implementation of a one-day trip program and the establishment of six community learning bases, including Historical Community, Uncle Swing's Fish Pond, Local Cooking, Grandma Thongdee Garden House, House of Boat Museum, and Happy Vegetable Plots. Moreover, the community product, wicker hats, has been developed to meet product standards, and 20 interpreters have been trained. Tourism-related media, such as Facebook and YouTube channels, have been created to promote and sell community products. As a result, the community has generated income of 144 USD from product sales, 388 USD from tourism activities, and has accumulated funds totaling 53 USD. Additionally, a tourism management group has been established, leveraging community resources to create and enhance their value.